2017
DOI: 10.1007/s00784-017-2259-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single- and double-layered resorbable membranes and platelet-rich fibrin on bone healing

Abstract: Histopathologic evaluation has been carried out regarding the effect of platelet-rich fibrin and collagen membranes applied on bone recovery. Our objective is to contribute to barrier membrane studies that continue to guide and accelerate bone recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The scarce angiogenesis that was observed, in comparison with that obtained by the other groups, played a crucial role in bone neogenesis and in all regenerative processes because sufficient nutritional support is essential [30]. Fibrous connective tissue, which prevents osteogenesis entirely or partially [32], was observed at the base of the Ca-Ms (Fig 5b). It is hypothesized that cells cannot perform matrix calcification due to the lack of bone-derived growth and differentiation factors in bone defects [33].…”
Section: Discussionmentioning
confidence: 73%
“…The scarce angiogenesis that was observed, in comparison with that obtained by the other groups, played a crucial role in bone neogenesis and in all regenerative processes because sufficient nutritional support is essential [30]. Fibrous connective tissue, which prevents osteogenesis entirely or partially [32], was observed at the base of the Ca-Ms (Fig 5b). It is hypothesized that cells cannot perform matrix calcification due to the lack of bone-derived growth and differentiation factors in bone defects [33].…”
Section: Discussionmentioning
confidence: 73%
“…The rats were divided into three experimental groups using one layer of collagen membrane, two layers of collagen membranes and platelet-rich fibrin (PRF) membranes and a control group without any covering membrane. After 7 and 28 days, the histomorphometric analysis showed that the group that received PRF membranes had higher level of bone neoformation and a lower level of fibrosis when compared with the other groups [22].…”
Section: Discussionmentioning
confidence: 94%
“…Faot, Deprez, Vandamme, Camargos, Pinto, Wouters, van den Oord, Quirynen and Duyck [8] also reported similar ndings regarding the reduction of trabecular connectivity (Tb.Pf) during early bone healing periods in tibiae of rabbits treated with standard PRF membranes. The fact of PRF had a limited effect on bone repair can be associated with the signi cant decrease of release growth factors, such as TGF-ß1, and PDGF, after 3, 7, and 14 days, which does not seem to be long enough to stimulate the bone defect environment [41,42]. Moreover, the histological description of PRF group samples showed that bone healing occurs along the membrane but not inside the PRF clot.…”
Section: Discussionmentioning
confidence: 99%